Biology of Rhizoprionodon lalandii (Elasmobranchii: Carcharhinidae) captured by the artisanal fishery of Margarita Island, Venezuela - Tagliafico, Alejandro (2015)
Rhizoprionodon lalandii is a small shark (< 1.5 m) classified as Data Deficient by IUCN; however, in Venezuelan coastal waters, it represents one of the most captured species, with daily landings in many areas of the country, being an important component of traditional dishes with high demand and with an increased economical value in local markets. Due to the lack of biological information, the present work studied some reproductive and feeding aspects, with the main objective to contribute with base-line information for necessary sustainable management of the fishery. Samples were taken in two landing ports and two local markets once a week between January 2006 and December 2007. Total length (Lt), sex and maturity were evaluated for a total of 656 individuals with an average length of 56 ± 9 cm of Lt. Additionally, 108 stomachs were taken for the diet analysis. Significant differences were found in the overall sex ratio, with 54 % females (F), and 46 % males (M), and also in the embryos (60 % F, 40 % M), 45 % of the individuals were below average maturity length and 22 % of the females were gravid. Females reach maturity length (53 cm) before males (57 cm). Maximum fecundity was 5 embryos, with a maximum total length of 30.1 cm. Reproductive patterns were not clear throughout the years; nonetheless, between November and February the birth season was intense, with the highest rates of pregnant females and embryos with most length. The species principally feeds on fishes and, in less scale, cephalopods. The calculated trophic level was 3.7. We strongly recommend to fix a minimum length of capture (> 57 cm de LT), ban the catches of pregnant females and the application of a banned season of at least four months per year, to preserve the economic benefits of this fishery.